A Comparison of the Existing Wellness Programs in Neurosurgery and Institution Champion's Perspectives. Issue 5 (16th October 2018) - Wolfe, Stacey Quintero; West, James L; Hunt, Matthew A; Murad, Gregory J A; Fox, W Christopher; Dow, Jamie; Morone, Peter J; Wellons, John C; Podet, Adam; Wilson, Jason; Wu, Julian K; Spiotta, Alejandro M; et al.
Abstract: Once the accepted norm during Harvey Cushing's time, the mantra of work to the exclusion of family and lifestyle is now recognized as deleterious to overall well-being. A number of neurosurgical residency training programs have implemented wellness programs to enhance the physical, mental, and emotional well-being of trainees and faculty. This manuscript highlights existing organized wellness education within neurosurgery residency programs in order to describe the motivations behind development, structure, and potential implementation strategies, cost of implementation, and identify successes and barriers in the integration process. This manuscript is designed to serve as a "how-to" guide for other programs who may identify a need in their own trainees and begins the discussion of how to develop wellness, leadership, grit, and resiliency within our future generation of neurosurgeons.